ICAST2000 2nd International Conference on Advances in Strategic Technologies, 15-17th August 2000, Renaissance Palm Garden, Putrajaya - International Conference on Advances in Strategic Technologies 2000 : Putrajaya); Universiti Kebangsaan Malaysia. The Faculty of Engineering (Bangi : Universiti Kebangsaan Malaysia, 2000)
Frontier technologies for the 21st century
Keywords: Technological innovations